Analisis kepuasan Analisis Kepuasan Pengguna Terhadap Penggunaan Aplikasi Transportasi Online Dengan Metode Unified Theory Of Acceptance And Use Of Technology - Geri Esmemed; Gusmelia Testiana; Fathiyah Nopriani (Journal of Computer and Information Systems Ampera, 2021)
This study aims to determine the level of user satisfaction with the use of online transportationapplications in the Raden Fatah State Islamic University Palembang using the unified theoryof acceptance and use of technology (UTAUT) method. This study uses all the variables in theUTAUT methods, including moderation. The data in this study were collected using aquestionnaire distributed to 298 respondents in the Raden Fatah State Islamic UniversityPalembang. Data analysis was performed using descriptive analysis, simple regression analysisand moderated regression analysis. The results of this study indicate the level of usersatisfaction with the use of online transportation applications in the Raden Fatah State IslamicUniversity Palembang is 77.69%. From this percentage, it can be concluded that the use ofonline transportation applications has been declared satisfied, especially within the RadenFatah State Islamic University of Palembang.